Diachronic Identity, Variability and Homonymy in the Etymologization of Soundsymbolic Words (on the material of Slavic languages) - Koleva-Zlateva, Zhivka (Slavica, 2022)
In etymology, the diachronic identity of words and morphemes is proved by the joint application of the comparative historical method regarding sound form and the method of semantic typology (semantic parallels) regarding semantics. This rule is fully applicable, however, only for arbitrary signs of the languagein which the nonexclusivity of phonetic laws has been proved. The article shows that the definition of diachronic identity insound symbolic words is complicated by their very nature as iconic signs, processed by the right hemisphere of the brain, which predetermines their disobedience to phonetic laws, formal variability and the rather frequent presence of homonyms. The pragmatic, functional and structural properties of sound symbolic words are also taken into account.